How to Learning Arithmetic Sequences with Project-Based Learning in Terrace Culture? - Nurhikmayati, Iik; Kania, Nia (Mathematics Education Journal, 2021)
Integrating mathematics into local culture is a way to enhance students' interest in local wisdom. The concept of mathematics is explored to find out the existence of mathematics in society's culture which has not been seen so far. The Mathematical concept is used to explore the existence of mathematics in terrace culture on the Panyaweuyan terrace of Majalengka city. This study to describe the result of exploratory project-based learning of the Panyaweuyan terrace with this kind of exploratory research. The exploring of the relationship between the terrace culture of panyaweuyan and concept mathematics, especially in the concept of arithmetic sequences is analyzed and described through literature studies, observation, and interviews with 4 informants who are local farmers. The results that there is a relationship between the arithmetic sequence concept with the local culture of Panyaweuyan Majalengka city. The results of the study stated that each mound on each step on the Panyeweuyan terraces was formed through an arithmetic sequence formula. Farmers in Panyaweuyan terraces are naturally able to make terraces according to the arithmetic sequence formula without knowing the basics of mathematics. Therefore, the concept of mathematics is part of local culture which has an important role in preserving the nation's culture. DOI: https://doi.org/10.22342/jpm.15.2.13800.133-144